Study lucuma powder performance from fresh fruit - Lavado Soto, Mooner Aurelio (2012)
The aim of the study is the principal parameters establish or to determine for the production of flour of eggplant of excellent quality, depending on the temperature, time of dried and size of the particles of flour, which finally define the performance of the process. One used fruits in his ideal condition of maturity organoléptica, for preventing it from oxidizing for action of the enzimas, there was in use a solution of 80 parts for million (ppm) of metabisulfito of potassium. The temperature of dried was of 65°C during 16h, which was carried out in a dryer of trays of stainless steel, with control of temperature and time. (Dryer of 20 trays of 50 X 40 cm c/u). For the grinding there was used a molino of hammer of stainless steel of 10kg/h, the flour being obtained by size of minor particle of 0.5 mm.